LEARNING OBSTACLE YANG DIALAMI PESERTA DIDIK DALAM MENYELESAIKAN SOAL-SOAL INTEGRAL TAK TENTU - ade sopiati; usep kosasih (UJMES (Uninus Journal of Mathematics Education and Science), 2018)
This research is motivated by the mistakes that students did in solving the indefinite integral problems. Such mistakes might occur because of learning problems experienced by the learners. The purpose of this study is to examine the types of learning barriers experienced by learners in solving the indefinite integral problems. This research is a descriptive research with qualitative approach. The subjects of this study were the students of class XII who had experienced the indefinite integral problems. The subject was selected by a purposive sampling technique. The data were collected by using a triangulation technique. The findings showed that the LO experienced by the learners in solving the indefinite integral problems, were: (1) mistakenly understanding the association of derivatives with the indefinite integral, (2) being erroneous in deciphering the indefinite integral problems in the form of algebraic functions (polynomials, roots, and fractions) related to the operations, and (3) the students did not write “+c and dx” in integrating steps and integrating results. The LO focused on epistemological learning obstacle.